The simplified GLIM criteria for assessment of malnutrition and its correlation with clinical outcomes in Crohn’s disease patients - Xiaomei Song; Xiaomei Song; Xiaomei Song; Xiaoxin Zhou; Xiaoxin Zhou; Hao Wang; Hong Guo; Jian Yang; Jian Yang (Frontiers in Nutrition)
ObjectivePatients with Crohn’s disease (CD) commonly experience malnutrition. The Global Leadership Initiative on Malnutrition (GLIM) criteria, a novel approach to assessing malnutrition, has been validated in some diseases. However, there are limited studies in CD patients. This study aimed to investigate the applicability and effectiveness of the simplified GLIM criteria for evaluating the nutritional status of patients with Crohn’s disease. Additionally, it sought to evaluate the correlation between malnutrition defined by simplified GLIM and clinical outcomes.MethodsA retrospective cohort study was conducted with 386 patients with CD. Data were extracted from the medical records, including demographic and clinical characteristics. All patients were evaluated using the simplified GLIM criteria. The prevalence of malnutrition was reported and the relationship between malnutrition and clinical outcome was analyzed.ResultsThe prevalence of malnutrition among patients with CD was 73.6%, with 36.5% classified as moderate malnutrition and 37.0% classified as severe malnutrition. The malnourished group had significantly higher Crohn’s Disease Activity Index (CDAI) scores compared to the non-malnourished group (p < 0.001). Furthermore, the malnutrition group exhibited significantly lower levels of specific nutritional indicators, including hemoglobin (p = 0.040), albumin (p = 0.015), and prealbumin (p = 0.021). The median duration of follow-up in the cohort was 15.2 weeks. The results indicated that malnutrition, as assessed by simplified GLIM, independently influenced endoscopic remission (p = 0.033). Additionally, the duration of disease (p = 0.021), C-reactive protein (p = 0.014) and prealbumin (p = 0.014) were independent factors influencing endoscopic remission in patients with CD.ConclusionMalnutrition identified using the simplified GLIM criteria is associated with age, CDAI, behavior, hemoglobin, and albumin, providing prognostic value for endoscopic remission in CD patients.